A flexible metamodel architecture for optimal design of Hybrid Renewable Energy Systems (HRES) – Case study of a stand-alone HRES for a factory in tropical island. (20th June 2019) - Roth, Anastasia; Boix, Marianne; Gerbaud, Vincent; Montastruc, Ludovic; Etur, Philippe
Abstract: The energy sector is mutating with an increasing share of renewable energy. Renewable energy developers are facing new challenges, in particular sizing systems that combine multiple production sources and storage devices to match demand. Accordingly, this paper proposes a flexible metamodel architecture and a C++ software implementation for the grassroots design of Hybrid Renewable Energy System (HRES). The metamodel enables one to build optimization problem formulated as a Mixed Integer Linear Problem (MILP) with a tailor-made objective function to find the optimal size of HRES. The flexibility of the metamodel lies in its ability to handle many hybrid system configurations for three common types of usages of HRES, either for onsite demand, remote demand or a combination. It is demonstrated with two specific case studies, a stand-alone HRES composed of PV panels, battery set, and a diesel generator; and a factory in a tropical island. This paper contributes to a better adoption of cleaner production systems since it provides to decision makers a tool for HRES assessment. Highlights: A flexible metamodel for optimal design of Hybrid Renewable Energy System is proposed. We use it to model a stand-alone HRES: PV panels, battery set and diesel generator. The sensitivity of the model to consumption profiles is highlighted. Results for a real factory in a tropical island are discussed.